The Impact of EU Regional Policy on Eastern European Countries: Development Prospects for Ukraine - Кравець, Анастасія Юріївна; Цурканова, Ірина Олександрівна (Київський національний університет імені Тараса Шевченка, 2025)
The article examines the impact of the European Union's regional policy on Eastern European countries with an emphasis on comparing EU member states (Poland, Romania) and Eastern Partnership countries (in particular, Ukraine). The mechanisms through which regional policy contributes to socio-economic development and integration processes are analysed. Particular attention is paid to the opportunities and challenges for Ukraine, which is on the path to EU membership. The authors formulate practical recommendations based on the experience of Eastern European countries that have already adapted regional development policy in accordance with European standards. This topic and its research are relevant in view of Ukraine's strategic course for joining the EU. The experience of regional policy shows how even after radical transformations, countries can achieve success provided that policies are properly adapted. In the context of decentralization, the growing role of communities and the need for national cohesion in times of war, this topic acquires not only scientific but also practical importance. Its interdisciplinary (politics, management, regional studies, economics) also contributes to integration into the international scientific discourse, which has a positive impact on globalization. The relevance of borrowing the best practices of the EU to increase the regional resilience of Ukraine against the background of security and economic challenges caused by the full-scale military aggression of the Russian Federation is substantiated. The study proposes a new approach to the typology of regional development using the classification matrix of regions taking into account the concept of «regional political resilience». A review of the modern scientific discourse on the definition of the concept of «region», its role in the national space and in the context of globalization is conducted. The approaches of domestic and foreign scientists to the assessment of regional policy are analysed.

У статті досліджується вплив регіональної політики Європейського Союзу на держави Східної Європи з акцентом на порівняння країн-членів ЄС (Польща, Румунія) та країн Східного партнерства (зокрема, України). Проаналізовано механізми, за допомогою яких регіональна політика сприяє соціально-економічному розвитку та інтеграційним процесам. Особливу увагу приділено можливостям та викликам для України, яка перебуває на шляху до членства в ЄС. Автори формулюють практичні рекомендації на основі досвіду східноєвропейських держав, що вже адаптували політику регіонального розвитку згідно з європейськими стандартами. Виявлено, що навіть після радикальних трансформацій, країни можуть досягти успіху за умови правильної адаптації політик. У контексті децентралізації, зростання ролі громад, потреби у згуртованості країни в умовах війни — ця тема набуває не лише наукової, а й практичної ваги. Її міждисциплінарність (політика, управління, регіоналістика, економіка) також сприяє інтеграції до міжнародного наукового дискурсу, що позитивно впливає на глобалізацію. Обґрунтовано актуальність запозичення кращих практик ЄС для підвищення регіональної стійкості України на тлі безпекових та економічних викликів, спричинених повномасштабною воєнною агресією рф. У дослідженні запропоновано новий підхід до типологізації регіонального розвитку із застосуванням класифікаційної матриці регіонів з урахуванням поняття «регіональної політичної резильєнтності». Проведено огляд сучасного наукового дискурсу щодо визначення поняття «регіон», його ролі в національному просторі та в умовах глобалізації. Проаналізовано підходи вітчизняних і зарубіжних науковців до оцінки регіональної політики.
Вплив регіональної політики ЄС на держави Східної Європи: перспективи розвитку для України
Keywords: regional policy; European Union; Eastern Europe; integration; Ukraine; regional political resilience; регіональна політика; Європейський Союз; Східна Європа; інтеграція; Україна; регіональна політична резильєнтність